Digital Parenting; Strengthening Religious Concept Nafs in the Prevention of Child Pornography - Siti Zazak Soraya (FITK UIN Walisongo, 2022)
Children of the digital generation are a vulnerable group facing the potential dangers of the internet. Pornography exposure is one of the harmful effects of the internet on children. Parents play a critical role in ensuring their children's safety from cybercrime. This study aimed to explore the role of parents and the problems encountered in strengthening the concept of religious nafs of Al-Ghazali to prevent child pornography through digital parenting. Eight participants were involved in this study. This study was a descriptive qualitative study. The researcher gathered the data in this study through interviews, observation, and documentation. Data were analyzed using an interactive model that included data condensation, data display, and drawing conclusions. The finding of the study revealed that (1) Parents' method of strengthening religious concept nafs Al-Ghazali for their children was through religious rituals such as praying five times a day, fasting, and religious engagement such as reading the holy Qur'an to prevent child pornography; (2) The role of parents in strengthening religious concept nafs included modeling, controlling, and building attachment; and (3) parental barriers to strengthening religious concept nafs were gadget addiction, parental burnout, and lack of self-disclosure.